From undergraduate medical education to pre-registration house officer year: how prepared are students? - Wall, David; Bolshaw, Andrea; Carolan, Justine (Medical teacher, 2006)
Studies in the United Kingdom show that the first year of being a new doctor is a difficult transition from being an undergraduate medical. These doctors feel ill-prepared by their undergraduate medical student education and ill-equipped for their new role. This is a questionnaire study looking at 193 pre-registration house officers (PRHOs) and 212 consultant educational supervisors within the West Midlands Deanery in England, UK. The study asked how well prepared these new doctors were in seventeen basic subject areas (using a General Medical Council based template), and also, using the same template, how well prepared their consultant educational supervisors felt they were. Statistical testing included ranking of subject areas for each group, reliability testing and comparisons of views of house officers and consultants. Both groups ranked communication skills areas highest (best prepared) and ranked basic doctoring skills (such as prescribing, treatment, decision making and emergencies) lowest. House officers rated themselves significantly higher than did their consultant supervisors in thirteen out of the seventeen areas tested. In discussion, we ask if we have gone too far in teaching effective communication at the expense of basic doctoring skills. We also consider whether indeed young doctors have an inflated opinion of their own competencies, or are the older generation seeing the world through rose tinted spectacles?